The active female : health issues throughout the lifespan - Norman, Reid L.; Zumwalt, Mimi; Robert- McComb, Jacalyn J. (Springer New York, 2014)
The purpose of the The Active Female: Health Issues Throughout the Lifespan, 2nd Edition is twofold: (1) to increase the awareness of wellness and fitness issues for active females and their family members; and (2) to provide an avenue for medical practitioners, allied health professionals, health educators, and certified individuals in sports medicine to gain critical, updated knowledge of a field specific to active females.  Part I of the book offers a foundation to help the reader understand the interrelationship among body image concerns, the female reproductive cycle, and musculoskeletal anatomy/physiology of females that makes their health risks and concerns unique.  Reproductive health is discussed by a prominent researcher in reproduction/endocrinology. An overview of the Female Athlete Triad which is a syndrome of three interrelated conditions (isordered eating, menstrual disturbances and bone loss) is presented in Part II. Physicians and certified professionals in sports medicine discuss the individual components of the triad, relating not only to the athletic female but also to the recreationally active woman throughout the lifespan.  In Part III, Prevention and management of common musculoskeletal injuries is addressed by a female orthopedic surgeon who sub-specializes in treating female athletes. Finally, appropriate exercise and nutritional guidelines for active females are discussed in Parts IV-V of the book by certified professionals and licensed physicians in sports medicine.  An invaluable addition to the literature, The Active Female: Health Issues Throughout the Lifespan, 2nd Edition will be of great interest to physicians, allied health care practitioners, medical/other wellness educators, and students who are interested in advancing women's health issues.  Sports medicine specialists, family practitioners, gynecologists, team physicians, residents in sports medicine, athletic trainers, health educators, nurses, physicians assistants, physical therapists, sport psychologists, counselors, athletic trainers, and other members of the sports medicine team should also find this title of significant interest.